2017
DOI: 10.1101/gr.219493.116
|View full text |Cite
|
Sign up to set email alerts
|

Detecting ancient positive selection in humans using extended lineage sorting

Abstract: Natural selection that affected modern humans early in their evolution has likely shaped some of the traits that set presentday humans apart from their closest extinct and living relatives. The ability to detect ancient natural selection in the human genome could provide insights into the molecular basis for these human-specific traits. Here, we introduce a method for detecting ancient selective sweeps by scanning for extended genomic regions where our closest extinct relatives, Neandertals and Denisovans, fal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
172
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(176 citation statements)
references
References 76 publications
3
172
0
1
Order By: Relevance
“…. 1995), for which the ancestral Neanderthal-like allele has not been observed in 1,000s of modern human genomes and which has been pointed out before as under positive selection (Castellano et al 2014;Racimo et al 2014;Racimo 2016;Peyrégne et al 2017) We know that archaic hominins likely had certain language-like abilities (Dediu and Levinson 2013;Dediu and Levinson 2018), and hybrids of modern and archaic humans must have survived in their communities , underlining the large overall similarity of these populations.…”
Section: Cellular Features Of Neuronsmentioning
confidence: 93%
See 1 more Smart Citation
“…. 1995), for which the ancestral Neanderthal-like allele has not been observed in 1,000s of modern human genomes and which has been pointed out before as under positive selection (Castellano et al 2014;Racimo et al 2014;Racimo 2016;Peyrégne et al 2017) We know that archaic hominins likely had certain language-like abilities (Dediu and Levinson 2013;Dediu and Levinson 2018), and hybrids of modern and archaic humans must have survived in their communities , underlining the large overall similarity of these populations.…”
Section: Cellular Features Of Neuronsmentioning
confidence: 93%
“…Apart from their consequences for cognitive functions, it has been suggested that changes involved in synaptic plasticity might be interpreted in a context of neoteny Liu et al 2012;Peyrégne et al 2017;Sherwood and Gómez-Robles 2017), with the implication of delayed maturation in humans (Bednarik 2013) and a longer timeframe for brain development.…”
Section: Life History and Other Phenotypic Traitsmentioning
confidence: 99%
“…We additionally investigate three types of population genetic annotations that may be relevant to changes in cortical structure. Selective sweep regions are exceptionally long genomic regions of low diversity resulting from nearby selected alleles quickly rising in frequency to become fixed (i.e., non-varying) in the population 26 . One method for identifying such sweeps, Extended Lineage Sorting, can be used to detect putative selective events occurring over the last ~300-600 kya 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Selective sweep regions are exceptionally long genomic regions of low diversity resulting from nearby selected alleles quickly rising in frequency to become fixed (i.e., non-varying) in the population 26 . One method for identifying such sweeps, Extended Lineage Sorting, can be used to detect putative selective events occurring over the last ~300-600 kya 26 . Moving to more recent periods of evolutionary history, the Qx score determines if alleles at multiple loci associated with a multifactorial trait also display consistent differences in allele frequencies across existing human populations, which is taken as a signature of polygenic adaptation occurring following the separation of those populations (~50 kya) 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation